2020
DOI: 10.1021/acs.energyfuels.0c01234
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Oxidative Decomposition Behaviors of Different Sources of n-C7 Asphaltenes under High-Pressure Conditions

Abstract: Effects of pressure on thermo-oxidative decomposition of different sources of n-C7 asphaltenes were investigated at high pressure using a thermogravimetric analyzer under an air atmosphere. The n-C7 asphaltenes were extracted from different heavy and extra-heavy crude oils around the world and were thoroughly characterized by elemental analysis (EA), vapor pressure osmometry (VPO), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), and nuclear magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 75 publications
4
41
0
Order By: Relevance
“…However, when the oxidation of different n-heptane insoluble asphaltenes was compared, the highest oxygen incorporation in the initial oxidation period happened to correspond to the samples with the highest aromatic carbon content. 38 This suggested that aromatic oxidation to produce quinonoids (Figure 8) and the subsequent thermal decomposition of the quinonoids 39 were more important than aliphatic oxidation of aliphatic carbon. If this is indeed the case, then it is unfortunate, because oxidation of aromatic carbon is a less efficient reaction pathway for facilitating addition reactions and is, in fact, a pathway that can lead to ring opening of the aromatics.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the oxidation of different n-heptane insoluble asphaltenes was compared, the highest oxygen incorporation in the initial oxidation period happened to correspond to the samples with the highest aromatic carbon content. 38 This suggested that aromatic oxidation to produce quinonoids (Figure 8) and the subsequent thermal decomposition of the quinonoids 39 were more important than aliphatic oxidation of aliphatic carbon. If this is indeed the case, then it is unfortunate, because oxidation of aromatic carbon is a less efficient reaction pathway for facilitating addition reactions and is, in fact, a pathway that can lead to ring opening of the aromatics.…”
Section: Discussionmentioning
confidence: 99%
“…Decomposing structures by R–R bonds is less complicated than breaking R-A structures [ 56 ]. Additionally, a higher asphaltene content, the presence of thiophenes and pyrroles prevails; therefore, more time is required for their cracking [ 49 ]. In addition, the first cracked products can polymerize and form coke.…”
Section: Resultsmentioning
confidence: 99%
“…X-ray photoelectron spectrometry analysis was obtained in a PHOIBOS 150 1D-DLD analyzer (SPECS, Berlin, Germany). The procedures are described elsewhere [ 49 ]. Based on these results, average representative molecules for both fractions were constructed and optimized by density functional theory applying Becke’s three-parameter and Lee-Yang-Parr functions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The asphaltenes can have a gaseous conversion, due to the partial pyrolysis and evaporation of light molecular weight hydrocarbons [51]. It is reported that asphaltene molecules isolated from different crude oils decompose at high temperatures between 400 and 500 • C [19,23,52].…”
Section: Non-isothermal Thermogravimetric Experimentsmentioning
confidence: 99%